O czułym wychowawcy słów kilka - Konarzewska, Anna (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
Janusz Korczak understood the role of the educator as a process of searching and wandering. He compared the actions of an educator to the medical profession. Although his pedagogical writings and books were written almost a century ago, they are still relevant today. Korczak’s timeliness is manifested primarily in the equality of the child and the educator. The constant question “why?” contains the element of an explorer of the child’s personality, but above all it is the quintessence of being human in building interpersonal relations. His philosophy of education still inspires many educators today. The world of VUCA poses countless challenges to contemporary educators. What would Korczak advise them?